CLOUD COMPUTING IN AGRICULTURE – AN BOON - GOKILA R; UMA MAHESWARI K (Innovare Journal of Agricultural Sciences, 2019)
In India, around 75% of the population earns its livelihood from agriculture. It fulfills the basic need of human beings and animals. It is an important source of raw material for many agro-based industries. India’s geographical condition is unique for agriculture because it provides many favorable conditions. There are plain areas, fertile soil, long growing seasons, wide variation in climatic condition, etc. Apart from unique geographical conditions, India has been consistently making innovative efforts using science and technology to increase production. In that one the major booming sector is cloud computing, i.e., Cloud-agro revolution. Due to my passion in agriculture and tied to implement my research area in cloud. Today’s agriculture is embedded with advance services such as GPS and sensors [1] which is used to communicate with each other and also used to analyses and exchange Agri Information’s among them. IT provides services in the form of cloud to agriculture. Agri-cloud and IT offers expertise service to farmers regarding cultivation of crops, pricing, fertilizers, and diseases details and methods of cure to be used etc. In this field, there are huge discoveries, suggestions regarding modern techniques for cultivation, usage of fertilizers, can obtain cultivation history of the region, etc. In this paper, our study was based on is to design and implement a simple cloud-based application on Agriculture System which is based on agri-cloud that enhance agriculture production and also enhance the availability of data related to research projects in field.